O discurso da educação escolar nas histórrias em quadrinhos do Chico Bento - Daniela Amaral Silva Freitas (2008)
This work presents a study of the school education discourse functioning in Chico Bento comics. Through methodological procedures inspired in Michel Foucault's discourse analyzes, this research analyzes which meanings about school are divulged in this artefact. Using concepts of curriculum and culture based on the post-structuralism approach and concepts from Michel Foucault's theory power, subjectivity and discourse this dissertation analyzes the elements that constitute the Vila Abobrinha Municipal School, broadly divulged in the Chico Bento comics. The analyzes shows this school as a disciplinary institution that, through power techniques, tries to conform the students body to a strict space and time and teaches adequate behaviors to a good school performance. It also shows that, in the studied comics are disposed many and heterogeneous techniques of teaching subjectification. As a whole, these techniques produces and divulges the following teaching subjectivities: Versatile: compromised, moralistic, affective, careful and loving; "hysterical and irritated"; and romantic and asexual. It still analyzes different students bodies production practices to show how the students corporeity, formed by clothes and adornments, gestures and behaviors, have gender marks. There is a clear distinction between the masculinity and the femininity traces when the students are presented in the comics. The argument developed in this dissertation is that, despite of the school education discourse in Chico Bento comics divulge a disciplinary school, with spaces and times compartmentalized and full of rules, with a curriculum that teaches more procedures considered appropriate than knowledge (related to the school topics) and with pedagogical subjects (teacher and students) that have a lot of marks already broadly and accepted in our society, its constituents effects are not completely guaranteed because there is, in the interior of the discourse, conflicts, gaps and resistances in what is taught by the cultural device curriculum the Chico Bento comics.